Penerapan Model Pembe Lajaran Learning Cycle 5E Pada Materi Konflik Sosial - Wesli Erwanci Seu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this study was to find out the application of the Learning Cycle 5E Learning Model at Grade XI IPS SMA Efata Soe. This type of research was Classroom Action Research (PTK) which was intended to improve classroom learning. The subject of this study was 23 students at Grade XI IPS SMA Efata Soe. This research was conducted in two cycles. In each cycle, there were 2 meetings, and an evaluation or test was held at the end of the meeting. Data collection techniques used observation sheets, interviews, tests, and documentation. The data analysis technique used qualitative and quantitative data analysis. This research shows that there was an increase in student learning outcomes in learning sociology in Cycle II. Sociology learning outcomes at the Pre-Cycle meeting total scores of 1,560 with an average of 67.8 and Cycle 1 total scores of 1,640 with an average of 71.30 while Cycle II total scores of 1,910 with an average of 83.8. This study shows that the success criteria set by the researcher were 80% above the KKM 72, so this research was said to be successful because it has achieved success indicators.